Effect of circumcision on urinary tract infection in boys - TOPUZOĞLU, AHMET; ALPAY, HARİKA; GÖKCE, İBRAHİM (TURKISH PEDIATRICS ASSOC, 2011)
Aim: To assess the effect of circumcision after the newborn period on recurrence of urinary tract infections (UTI) in boys. Material and Method: Fifty-six boys ranging in age from 1 to 70 months (median 5 months) with UTI were evaluated retrospectively. Renal ultrasonography and dimercaptosuccinic acid scan were performed in all patients at admission. Voiding-cystourethrography was performed in selected patients. Thirty-three boys had no underlying vesicoureteral reflux (VUR), 23 boys had VUR grade 1-3. Regular urine samples were cultured to detect UTI, defined as a single species with > 10(5) colony-forming units/ml. Number of UTI per urine sample (number) and per follow-up time (month) were compared before and after circumcision. Results: In the whole group; median UTI per sample was 0.33 (IR; 0.21) before circumcision and 0.0 (IR; 0.50) after circumcision, median UTI per month was 0.37 (IR; 0.51) before circumcision and 0.0 (IR; 0.0) after circumcision. When the analysis was done seperately, UTI episodes were significantly lower after circumcision both in patients with no underlying urinary tract anomaly and patients with low grade reflux. Conclusions: This study suggests that circumcision after the newborn period decreases recurrence of urinary tract infections in preschool boys with and without reflux. (Turk Arch Ped 2010; 45: 137-40)
Keywords: Child; circumcision; urinary tract infection; 1ST YEAR; VESICOURETERAL REFLUX; RISK; BACTERIURIA; PREVENTION; PREPUCE; HISTORY